Migraine Headache in an Employed Population: Demographics, Health Risks, Pharmaceutical Utilization, and Productivity Loss. Issue 8 (9th August 2022) - Burton, Wayne N.; Schultz, Alyssa B.; Shepherd, Martha E.; Hines, David
Abstract : This study is significant to clinicians because migraine is generally common among working age adults. This study also found a startlingly high percentage of migraineurs and other employees with prescriptions for opioids. Clinicians should treat migraines according to accepted treatment guidelines for opioid use. Abstract : Objective: Demographics, health risks, pharmaceutical utilization, and other characteristics of adults with and without migraine who were employed by a school district in the southern United States were compared. Methods: A total of 4528 employees completed a health risk appraisal. A diagnosis of migraine was reported by 11%. Employees with and without migraine were compared on several measures. Results: Demographic and health risk differences were observed among the comparison groups. One-fifth of migraineurs had a prescription for an opioid, which was associated with very high average annual health care costs (17, 791) compared with migraineurs without opioid (3907). Conclusions: Migraine is common in the workforce. Employers may want to educate employees with migraine about evidence-based treatments. Benefit plan design should be consistent with current accepted treatment guidelines for opioid use.